2004
DOI: 10.1002/jnr.20089
|View full text |Cite
|
Sign up to set email alerts
|

Dibenzocyclooctadiene lignans from Schisandra chinensis protect primary cultures of rat cortical cells from glutamate‐induced toxicity

Abstract: A methanolic extract of dried Schisandra fruit (Schisandra chinensis Baill.; Schisandraceae) significantly attenuated the neurotoxicity induced by L-glutamate in primary cultures of rat cortical cells. Five dibenzocyclooctadiene lignans (deoxyschisandrin, gomisin N, gomisin A, schisandrin, and wuweizisu C) were isolated from the methanolic extract; their protective effects against glutamate-induced neurotoxicity were then evaluated. Among the five lignans, deoxyschisandrin, gomisin N, and wuweizisu C significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 50 publications
1
66
0
Order By: Relevance
“…Structural integrity as indicated by the decrease in sensitivity to Ca 2+ stimulated mitochondrial permeability transition in-vitro, was further evidenced by decrease in the extents of mitochondrial malondialdehyde (MDA) production, Ca 2+ loading, and cytochrome c release (Chen, Chiu et al 2008). Sch B also shown to have protection against L-glutamate induced neurotoxicity and the protection was associated with 1) an inhibition of the increase of intracellular [Ca 2+ ]; 2) an improvement in the glutathione defense system, the level of glutathione, and the activity of glutathione peroxidase (GPx); and 3) an inhibition in the formation of cellular peroxide (Kim, Lee et al 2004). Recently Sch B was reported to have protection against amyloid beta and homocysteine induced neurotoxicity in PC12 in-vitro system (Song, Lin et al;Wang and Wang 2009).…”
Section: Neuroprotective Potential Of Sch Bmentioning
confidence: 99%
“…Structural integrity as indicated by the decrease in sensitivity to Ca 2+ stimulated mitochondrial permeability transition in-vitro, was further evidenced by decrease in the extents of mitochondrial malondialdehyde (MDA) production, Ca 2+ loading, and cytochrome c release (Chen, Chiu et al 2008). Sch B also shown to have protection against L-glutamate induced neurotoxicity and the protection was associated with 1) an inhibition of the increase of intracellular [Ca 2+ ]; 2) an improvement in the glutathione defense system, the level of glutathione, and the activity of glutathione peroxidase (GPx); and 3) an inhibition in the formation of cellular peroxide (Kim, Lee et al 2004). Recently Sch B was reported to have protection against amyloid beta and homocysteine induced neurotoxicity in PC12 in-vitro system (Song, Lin et al;Wang and Wang 2009).…”
Section: Neuroprotective Potential Of Sch Bmentioning
confidence: 99%
“…This study attempts to treat epilepsy by stabilizing the intra-synaptic actin skeleton Schisandra is a traditional Chinese medicine, which play roles in central inhibition and the role of tranquilization [15]. Studies have shown that schizandrine can prevent glutamate induced neuronal damage and antioxidation [10][11]. It not only effectively prevents the damage of the oxidative stress induced by glutamate in the rat brain, but also improves the memory function of mice by regulating the level of acetylcholine.…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports on the advantages of gomisins A, G, and J. Gomisin A protects the liver by blocking the metabolism of harmful chemicals by inhibiting cytochrome P450-3A4; 16 it also protects against neurotoxicity. 17 Gomisin G's anti-human immunodeficiency virus effects occur via the inhibition of human immunodeficiency virus type 1 reverse transcriptase. 18 Gomisin J has antioxidative effects in myoblast cells 19 and suppresses inflammatory responses.…”
Section: Introduction Imentioning
confidence: 99%